Determination of 23 related analytes in bone marrow fluid and hippocampus of C57BL/6 mice following cerebral ischemia–reperfusion injury by HPLC‐FLD - Zhang, Jing; Yang, Jun‐qing; Luo, Ying; Li, Jian‐sha; Gong, Tao; Huang, Su‐qiong; Xiong, Yan; Jiang, Xin‐hui (Biomedical chromatography, 2022)
The study of brain diseases has long been of interest to researchers worldwide, and stroke is the third leading cause of death that threatens human health. At the same time, cerebral ischemia–reperfusion injury is closely associated with high rates of disability and mortality. The conditions of the 6‐aminoquinolyl N‐hydroxysccinimidyl carbamate method for the derivatization of amino acids in the bone marrow fluid and hippocampus of C57BL/6 mice with cerebral ischemia–reperfusion injury were explored and optimized, such as the column temperature, concentration of derivatization reagents and mobile phase concentration. The mobile phase consisted of 20 mm sodium acetate solution (phosphoric acid to adjust pH 5.0) and 60% acetonitrile solution at a flow rate of 1 ml min−1. The 23 analytes were separated and determined in a gradient elution procedure; the correlation coefficient r was >0.9990 in the range 0.1–8.0 μg ml−1. The results showed that the content of relevant analytes was significantly changed in the cerebral ischemia–reperfusion injury model, and the method was suitable for the simultaneous determination of 23 amino acids in the bone marrow fluid and hippocampus of C57BL/6 mice.